Improvement of Basic Math Skills Through Realistic Mathematics Education (RME) in Early Childhood - Nahrowi Adjie; Suci Utami Putri; Finita Dewi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Realistic Mathematics Education (RME) is appropriate for basic education. It bridges abstract to concrete and useful Mathematics. RME emphasizes the importance of real contexts familiar to students and the process of constructing them. This study aims to determine the effect of RME on the ability of basic mathematical skills. The method used is Single Subject Research model experiment with two samples in the A-B-A' design. The results of the study: (1) The subjects before the treatment showed low basic mathematical abilities; (2) Learning activities with the RME approach are effective for improving basic math skills; and (3) the condition of the subjects after being given RME approach is in very good category. It can be concluded that RME has contributed to improve student learning outcomes and make learning more meaningful as learning is always associated and relevant with the reality of children's lives through selected themes.